Unusual presentation of uterine rupture in modern obstetrics - Manoli, Nandish; Gowda, Surakshith L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Rupture of uterus in modern obstetrics is rare. If not diagnosed in time maternal morbidity and mortality are very high. We are reporting a case initially referred as gravida2 abortion1 with breech presentation in active labour and was taken up for emergency LSCS, and on opening up a posterior uterine wall rupture was noted, later it was noted that the patient misled us by hiding her obstetric history of undergoing repeated MTPs. This case has been published in view of misleading history, variable clinical presentation & to emphasize the need of definitive surgeries in order to save the life of the individual.